Effect of positive end expiratory pressure on atelectasis in patients undergoing major upper abdominal surgery under general anaesthesia: A lung ultrasonography study. Issue 4 (April 2023) - Nair, Parvathy Ramachandran; Ramachandran, Rashmi; Trikha, Anjan; Anand, Rahul Kumar; Rewari, Vimi
Postoperative pulmonary complications vary in major upper abdominal surgery. The objective of this study was to assess the effect of positive end expiratory pressure on the incidence of atelectasis in patients undergoing major upper abdominal surgery under general anaesthesia using lung ultrasound. The patients were randomised into receiving either no positive end expiratory pressure (Group I) or positive end expiratory pressure of 5cm H2 O (Group II). Lung ultrasound was performed at various time points – baseline, 10 minutes, 2 hours after induction, during closure of skin and 30 minutes post extubation. The lung aeration as assessed by Total Modified Lung Ultrasound Score was worse in the Group I as compared to the Group II at 2 hours post induction. Driving pressure in Group II was significantly reduced compared to Group I. Application of positive end expiratory pressure, as minimal as 5cm H2 O, as a single intervention, helps in significantly reducing the Total Modified Lung Ultrasound Score after a duration of more than 2 hours and also attaining low driving pressures during intraoperative mechanical ventilation.